2013
DOI: 10.1080/00103624.2013.829083
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Toxicity of Germanium in Cucumber under Different Types of Germaniums

Abstract: The effects of germanium dioxide (GeO 2 ) and 2-carboxyethyl germanium sesquioxide (Ge-132) treatments on cucumber (Cucumis sativus L.) growth and Ge accumulation and toxicity were investigated. Accumulated Ge contents in plant treated with GeO 2 were two times greater than that in plants treated with Ge-132. Germanium accumulated primarily in the shoots in the GeO 2 treatments and in the roots in the Ge-132 treatments. In contrast GeO 2 was easily transported from roots to shoots. In cucumber fruit, the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
1
1
0
1
Order By: Relevance
“…The rationale behind this contention is that compared to Si, Ge shows a higher reactivity in terms to forms stable complexes with many functional groups (Pokrovski and Schott 1998) and therefore may interact with cell constituents such as cell walls and ligands in the cytosol. Therefore these patterns may depend on a saturation of potential binding sites needed before the element can be further transported along the shoot axis with the transpiration stream (Choi et al 2013). This is supported by our findings that root concentrations were similar in all experiments and plant species, while concentrations in above-ground plant parts varied greatly among species and the Ge concentrations supplied ( Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The rationale behind this contention is that compared to Si, Ge shows a higher reactivity in terms to forms stable complexes with many functional groups (Pokrovski and Schott 1998) and therefore may interact with cell constituents such as cell walls and ligands in the cytosol. Therefore these patterns may depend on a saturation of potential binding sites needed before the element can be further transported along the shoot axis with the transpiration stream (Choi et al 2013). This is supported by our findings that root concentrations were similar in all experiments and plant species, while concentrations in above-ground plant parts varied greatly among species and the Ge concentrations supplied ( Fig.…”
Section: Discussionsupporting
confidence: 82%
“…A number of mycorrhizal plants have a higher rate of photosynthesis (Birhane et al 2012), accumulate more auxins and cytokinins than non-mycorrhizal plants (Fusconi 2014) and are more resistant to abiotic stresses due to improved osmotic adjustment ____________________________________________________________________________________________________________________ (Al-Karaki 2006). The positive effects of AMF on vegetative and reproductive growth of some floricultural crops such as Rosa hybrida (Garmendia & Mangas 2012), Chrysanthemum morifolium (Sohn et al 2003), Eustoma grandiflorum (Pivonia et al 2010) and Antirrhinum majus (Asrar et al 2012) were reported. Inoculation with AMF enhanced flower production of Zantedeschia and Sparaxis tricolor as well as increased nutrient concentration in Zantedeschia tuber and Sparaxis tricolor corms (Scagel 2004;Scagel & Schreiner 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Германій виявлено в тканинах багатьох рослин. Накопичення Германію рослинами залежить від їхньої видової та сортової приналежності, стадії росту самої рослини, забезпеченості ґрунтів цим елементом, форми германієвих сполук у ґрунтах (неорганічна чи органічна), здатності ґрунтів зберігати лабільні форми Германію та кліматичних умов (Halperin et al, 1995;Choi et al, 2013;Wiche et al, 2017). Крім того, встановлено, що рослини, вирощені на нейтральних ґрунтах (рН = 6,6) накопичують Германію більше, ніж на слаболужних (рН = 7,8) (Wiche & Heilmeier, 2016).…”
Section: германій у рослинах і рослинних продуктахunclassified